Supported sulfide nanosheet catalyst as well as synthesis method and application thereof
By developing a supported sulfide nanosheet catalyst, the problems of high difficulty in removing pyridine and poor controllability of single-layer sulfide preparation during the hydronitrition gasoline were solved, and efficient hydronitrition reaction was achieved, with high activity and low cost.
Patent Information
- Application Number
- CN202311361871.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-19
AI Technical Summary
In the process of cracking gasoline hydronitride denitrogenation, especially the removal of pyridine containing alkaline nitrogen is more difficult, and the preparation and synthesis of single-layer sulfide is not highly controllable.
A supported sulfide nanosheet catalyst was developed with the chemical formula of M’-MS2/Al2O3, in which more than 90% of the sulfide (MS2) nanosheets were distributed in a single layer, and were prepared by hydrothermal treatment and vulcanization/reduction processes, and used for cracking gasoline hydronitrition and denitrification reaction.
The catalyst has high activity, low hydrogenation loss rate of aromatic hydrocarbons, simple and controllable preparation process, and low cost, which significantly improves the performance of the hydronitrition and denitrification reaction of cracking gasoline.
Smart Images

Figure CN119857502A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic denitrogenation of cracked gasoline, and in particular to a supported sulfide nanosheet catalyst and a synthesis method and application thereof. Background Art
[0002] Pyrolysis gasoline is a key byproduct of naphtha cracking to produce ethylene. Because it is rich in aromatics, it can be used as a high-octane gasoline component or used to extract chemical raw materials such as benzene, toluene, and xylene after hydrofining. However, in recent years, due to the heavy trend of upstream naphtha raw materials, the composition of pyrolysis gasoline has become more complex, especially the nitrogen content has increased significantly. The hydrodenitrogenation process (HDN) of pyrolysis gasoline can effectively remove nitrogen compounds, avoid poisoning the downstream aromatic extraction, and meet the restrictions on nitrogen content in the blending oil components. Therefore, studying the HDN catalytic process of pyrolysis gasoline is extremely important for the downstream aromatic extraction process and the blending oil components.
[0003] In the HDN process of cracked gasoline, it is most difficult to remove pyridine containing basic nitrogen, so the research on HDN of pyridine is particularly representative. As a commonly used industrial hydrorefining catalyst, supported transition metal sulfide catalyst has a high hydrogenation activity. At the same time, compared with precious metal hydrogenation catalysts, sulfide catalysts also have the advantage of low price. Previous studies have mainly focused on the preparation of Al2O3 supported multilayer sulfides, such as CN106268976A, CN103079697A, and CN102373078A. Previous studies have found that the preparation and synthesis of supported monolayer sulfides are not controllable, so there are few studies on their methods. However, due to the special structure and chemical environment of monolayer sulfides, it helps to improve their hydrogenation activity and thus promote the overall HDN reaction performance. Therefore, it is extremely meaningful to develop monolayer sulfide nanosheets and study their HDN catalytic reaction performance. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a supported sulfide nanosheet catalyst and its synthesis method and application. The majority (more than 90%) of the sulfide nanosheets in the catalyst of the present invention are single-layer, which is used in the hydrodenitrogenation reaction of pyrolysis gasoline, has high activity, low aromatics hydrogenation loss rate, and the preparation process is relatively simple and controllable.
[0005] The first aspect of the present invention provides a supported sulfide nanosheet catalyst, the chemical formula of the catalyst is M'-MS2 / Al2O3, wherein M' is an auxiliary metal selected from at least one of the VIII group elements Fe, Co or Ni, and M is a main metal selected from at least one of the VIB group elements Mo or W; more than 90% of the sulfide (MS2) nanosheets are in a single-layer distribution state.
[0006] Further, preferably, 90% to 98% of the sulfide (MS2) nanosheets are in a single-layer distribution state.
[0007] Furthermore, in the catalyst, based on the weight of the catalyst, the content of Al2O3 is 70% to 80%, the content of M in terms of oxide is 12% to 20%, and the content of M' in terms of oxide is 8% to 10%.
[0008] Furthermore, the length of the sulfide (MS2) nanosheets is 2.0 to 20.0 nm, preferably 2.0 to 10.0 nm, and more preferably 2.0 to 5.0 nm.
[0009] Furthermore, the specific surface area of Al2O3 is 250-400m 2 / g, preferably 300 to 375 m 2 / g; the amount of B acid on the Al2O3 surface is 5 to 25 μmol / g, preferably 10 to 20 μmol / g, and more preferably 12.5 to 15.5 μmol / g.
[0010] The second aspect of the present invention provides a method for preparing the above-mentioned supported sulfide nanosheet catalyst, comprising:
[0011] (1) Pseudo-boehmite is subjected to hydrothermal treatment, roasting and forming to obtain Al2O3;
[0012] (2) loading metals M and M' on Al2O3, aging and calcining to obtain a catalyst precursor;
[0013] (3) The catalyst precursor is subjected to sulfurization and reduction to obtain the catalyst.
[0014] Furthermore, in step (1), the average particle size of the pseudo-boehmite particles is 100 to 400 meshes, preferably 150 to 300 meshes.
[0015] Furthermore, in step (1), the pseudo-boehmite is subjected to conventional treatments such as drying, cooling and grinding before the hydrothermal treatment.
[0016] Furthermore, in step (1), the hydrothermal treatment is carried out under high temperature sealed dynamic stirring conditions. The hydrothermal treatment conditions are: temperature of 150-250°C, pH of 1.5-10.5, time of 4-24h, stirring speed of 200-800r / min, and heating rate of 0.5-2.0°C / min to the hydrothermal treatment temperature; preferably, the temperature is 150-200°C, the pH is 4.0-9.0, and the time is 4-12h; further preferably, the temperature is 180-200°C, the pH is 7.5-9.0, and the time is 6-12h.
[0017] Furthermore, in step (1), after the hydrothermal treatment, the product is first subjected to conventional treatments of separation, washing and drying. The washing is selected from one of distilled water, ethanol or isopropanol, preferably ethanol; the separation, such as suction filtration, uses one of a Buchner funnel or a sand core funnel, preferably a sand core funnel.
[0018] Furthermore, in step (1), the calcination is carried out under high temperature dynamic conditions. The calcination conditions are: temperature of 500-750°C, preferably 500-650°C, time of 3-8h, and heating rate to the calcination temperature of 0.5-4.0°C / min, preferably 1.0-4.0°C / min.
[0019] Furthermore, in step (1), the forming can be one of extrusion or tableting, preferably extrusion; the shape is one of cylindrical or cloverleaf, preferably cylindrical; the diameter and length of the cylinder are 1-5 mm and 2-6 mm, respectively, preferably 2-4 mm and 3-5 mm.
[0020] Furthermore, in step (2), the metal loading is carried out by equal volume impregnation.
[0021] Furthermore, in step (2), the metal M' is selected from at least one of the Group VIII elements Fe, Co or Ni, and the metal M is selected from at least one of the Group VIB elements Mo or W. The main metal (M) salt is ammonium molybdate tetrahydrate (NH4)6Mo7O 24 4H2O or ammonium tungstate hexahydrate (NH4) 6W7O 24 ·6H2O, and the auxiliary metal (M') salt is selected from at least one of Fe(NO3)3·9H2O, Co(NO3)2·6H2O and Ni(NO3)2·6H2O.
[0022] Furthermore, in step (2), when the main metal M is Mo, the molar ratio of the molybdenum salt to Al2O3 is 1:(50-80); when the main metal M is W, the molar ratio of the tungsten salt to Al2O3 is 1:(100-200). The molar ratio of the auxiliary metal salt to Al2O3 is 1:(20-50).
[0023] Furthermore, in step (2), the aging temperature is 20 to 50° C., preferably 30 to 40° C., and the aging time is 4 to 48 hours, preferably 16 to 24 hours.
[0024] Furthermore, in step (2), after aging, the separation and drying process is carried out. The drying conditions are: heating to 100-150° C. at 0.5-2° C. / min and drying for 8-24 hours.
[0025] Furthermore, in step (2), the calcination conditions are: the calcination temperature is 450-550°C, the calcination time is 3-8h, and the heating rate to the calcination temperature is 0.5-4°C / min.
[0026] Furthermore, in step (4), the sulfurized oil used for sulfurization is prepared from dimethyl disulfide (DMDS) and cyclohexane, and the sulfur content by mass is 400 to 5000 ppm.
[0027] Furthermore, in step (4), the sulfurization / reduction pressure is 2.6-3.0 MPa, the volume ratio of hydrogen to catalyst precursor is (10-100):1; the volume space velocity of sulfurized oil is 3.0-5.0 h-1. 1 , the vulcanization time is 20 to 40 hours.
[0028] Furthermore, in step (4), the sulfurization process is as follows: the temperature is raised to 150-180°C at a heating rate of 20-50°C / h, sulfurized oil is introduced, the temperature is further raised to 280-320°C at a heating rate of 20-50°C / h, and after maintaining for 20-40 hours, the temperature is naturally lowered to 150-180°C and the sulfurized oil is stopped. After the temperature is lowered to room temperature, the catalyst is stored in an inert atmosphere or an organic solvent for standby use.
[0029] Furthermore, the inert atmosphere may be Ar gas and / or He gas, preferably Ar gas. The organic solvent may be at least one of cyclohexane, benzene, toluene and xylene, preferably cyclohexane.
[0030] The third aspect of the present invention provides the use of the above-mentioned supported sulfide nanosheet catalyst in the hydrodenitrogenation reaction of pyrolysis gasoline.
[0031] Furthermore, the reaction conditions of the hydrodenitrogenation reaction are: reaction temperature of 220-400°C, reaction pressure of 2.5-4.0 MPa, volume space velocity of 0.5-4.0 h-1 1 , the hydrogen / oil volume ratio is 500-700.
[0032] Compared with the prior art, the present invention has the following advantages:
[0033] 1. The present invention provides a supported sulfide nanosheet catalyst with a chemical formula of M'-MS2 / Al2O3, wherein the sulfide (MS2) nanosheet is in a single-layer distribution state, and the sheet length is 2 to 20 nm. At the same time, the amount of B acid on the surface of the carrier Al2O3 in the catalyst is controlled to be 5 to 25 μmol / g. It is used for the hydrodenitrogenation reaction of cracked gasoline and has the characteristics of high activity and low aromatic hydrogenation loss.
[0034] 2. The present invention regulates the number of hydroxyl groups on the carrier surface by controlling the hydrothermal temperature, time and pH value of the carrier, thereby affecting the interaction strength between the carrier and the active component, forming a single-layer sulfide structure, and ultimately affecting the amount of B acid on the carrier and catalyst surface. Compared with the multi-layer transition metal sulfide sheet stacking structure, the utilization rate of the active center is high, and the entire preparation process is simple, easy, controllable and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is the XRD spectra of the catalysts of Example 5 and Example 11;
[0036] Figure 2 is the HRTEM image of the catalyst of Example 11;
[0037] Figure 3 XRD spectra of the carriers used in Example 2, Example 4 and Example 5;
[0038] Figure 4 This is the pyridine infrared spectrum of the carrier used in Example 2, Example 4 and Example 5. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with specific embodiments. The embodiments described below are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein. On the contrary, the present invention can be extended to all other methods and applications with the same functions.
[0040] In the context of this specification, X-ray diffraction (XRD) analysis of the catalyst was carried out on a D / max-2200PC X-ray diffractometer from Rigaku Corporation, Japan, using Cu Kα radiation, a tube voltage of 40 kV, a tube current of 30 mA, a scanning rate of 10° / min, and a scanning range of 10° to 80°.
[0041] In the context of this specification, the microscopic morphology and particle size of the catalyst were observed by high-definition transmission electron microscopy (HRTEM). 2The HRTEM test was performed using an F20 S-TWIN transmission electron microscope system. The system is equipped with a field emission gun with an accelerating voltage of 200 kV and a point resolution of 0.24 nm. The Nano Measurer software was used to observe and measure the size of more than 300 nanosheet particles selected in a random field of view, and the average length of the nanosheet was measured.
[0042] In the context of this specification, the proportion of sulfide nanosheets in the monolayer distribution state is obtained by counting the proportion of MS2 in the monolayer distribution in HRTEM. Monolayer distribution ratio = n (monolayer MS2) / n (all MS2), where n (monolayer MS2) and n (all MS2) are the number of monolayer MS2 sheets and all MS2 in the field of view, respectively, and the number of statistics is not less than 300.
[0043] In the context of this specification, a Nicolet 5700 Fourier transform infrared spectrometer was used for pyridine infrared (Py-FTIR) analysis. The scanning range was 1300-4000 cm- 1 , scanning times is 32 times, resolution is 4cm- 1 Take about 15 mg of sample, press and demould to obtain a self-supporting sheet, place it in a reaction pool, evacuate at 400℃ for 2h, cool to 50℃ to take the background, open the pyridine adsorption chamber valve until the catalyst pyridine adsorption is saturated, then program the temperature to 300℃, evacuate for 0.5h, and finally take the spectrum and remove the background. The specific calculation formula is shown in formula (1): Wherein the acid amount of B acid is in μmol / g; A (B acid) is 1540cm- 1 The integrated peak area of the characteristic peak at ; r is the radius of the self-supporting sample piece, in cm; w is the mass of the sample piece, in mg;
[0044]
[0045] In the context of this specification,
[0046] [Example 1]
[0047] Take 0.55g of citric acid and add it to 19.0g of distilled water to prepare an acidic solution with a pH value of 1.5 for standby use; take 10.0g of pseudo-boehmite (AlOOH·nH2O), grind it to 200 mesh after drying and cooling, transfer it to a 500mL hydrothermal crystallization reactor, add the above citric acid solution, stir it thoroughly at a speed of 600r / min, heat it to 180℃ at a rate of 0.5℃ / min, and keep it hydrothermally for 12h. After the reactor is cooled, wash the obtained solid with ethanol 3 times, filter it through a sand core funnel, and heat it to 550℃ at a rate of 1.0℃ / min in a dynamic air environment for 6h. The obtained solid powder is extruded into a cylindrical shape with a diameter and height of 3mm and 5mm respectively, which is recorded as the carrier Al2O3-1.5 (in the example of the present invention, Al2O3-x, where x represents the pH value of the above hydrothermal environment).
[0048] The saturated water absorption rate of the above Al2O3-1.5 carrier was measured. Take 0.232g of ammonium molybdate tetrahydrate and dissolve it in distilled water weighed according to the saturated water absorption rate, and soak an equal volume on 1.0g of Al2O3-1.5 carrier. After aging at 30℃ for 12h, dry it at 120℃ under dynamic air for 12h, and heat the obtained solid to 500℃ at a rate of 2℃ / min and maintain it for 6h to obtain a catalyst precursor. Take 4.0g of the above catalyst precursor and load it into a sulfurization reactor, and introduce 3000ppm sulfur content sulfurized oil prepared by DMDS and cyclohexane, and pass hydrogen at a pressure of 2.6MPa, and the volume ratio of hydrogen to catalyst is 100:1; heat the catalyst bed to 150℃ at a heating rate of 30℃ / h and start to introduce sulfurized oil, and the sulfurized oil space velocity is 4.0h -1 , continue to heat the catalyst bed to 320°C at a heating rate of 30°C / h, maintain it for 32 hours, then naturally cool it to 150°C and stop adding sulfide oil. After cooling to room temperature, store it in cyclohexane. The obtained catalyst SS1 is recorded as MS2 / Al2O3-1.5.
[0049] [Example 2]
[0050] The catalyst preparation method is the same as that in Example 1, except that the amount of distilled water required to dissolve the citric acid is changed from 19.0 g to 40.0 g; finally, catalyst SS2 is obtained.
[0051] [Example 3]
[0052] The catalyst preparation method is the same as that in Example 1, except that 0.55 g of citric acid is replaced with 0.55 g of acetic acid; finally, catalyst SS3 is obtained.
[0053] [Example 4]
[0054] The catalyst preparation method is the same as that in Example 1, except that 0.55 g of citric acid is added to 19.0 g of distilled water instead of adding citric acid, and finally catalyst SS4 is obtained.
[0055] [Example 5]
[0056] The catalyst preparation method is the same as that in Example 1, except that 0.55 g of citric acid is added to 19.0 g of distilled water instead of 1.58 g of ammonium bicarbonate being added to 200 g of distilled water, to finally obtain catalyst SS5.
[0057] [Example 6]
[0058] The catalyst preparation method is the same as that in Example 1, except that 0.55 g of citric acid is added to 19.0 g of distilled water instead of 1.92 g of ammonium carbonate being added to 200 g of distilled water, to finally obtain catalyst SS6.
[0059] [Example 7]
[0060] The catalyst preparation method is the same as that in Example 5, except that the carrier calcination conditions are changed from heating to 550°C at a rate of 1.0°C / min to heating to 700°C at a rate of 0.5°C / min, and finally catalyst SS7 is obtained.
[0061] [Example 8]
[0062] The catalyst preparation method is the same as that in Example 5, except that the main metal impregnation solution is changed from 0.232 g of ammonium molybdate tetrahydrate to 0.354 g of ammonium tungstate hexahydrate, and finally catalyst SS8 is obtained.
[0063] [Example 9]
[0064] The catalyst preparation method is the same as that in Example 5, except that 0.11 g of Fe(NO3)3·9H2O auxiliary metal salt is added to the main metal impregnation solution, and finally catalyst SS9 is obtained. In catalyst SS9, 93% of MoS2 nanosheets are in a monolayer distribution state.
[0065] [Example 10]
[0066] The catalyst preparation method is the same as that in Example 5, except that 0.08 g of Co(NO3)3·6H2O auxiliary metal salt is added to the main metal impregnation solution, and finally catalyst SS10 is obtained. In catalyst SS10, 95% of MoS2 nanosheets are in a single-layer distribution state.
[0067] [Example 11]
[0068] The catalyst preparation method is the same as that in Example 5, except that 0.08 g Ni(NO3)3·6H2O auxiliary metal salt is added to the main metal impregnation solution, and finally catalyst SS11 is obtained. Figure 2This is the HRTEM photo of catalyst SS11. Calculation shows that 97% of the MoS2 nanosheets are in a single-layer distribution state.
[0069] [Example 12]
[0070] The catalyst preparation method is the same as that in Example 5, except that the sulfidation temperature is changed from 320°C to 300°C, and finally catalyst SS12 is obtained.
[0071] [Example 13]
[0072] The catalyst preparation method is the same as that in Example 8, except that 0.08 g Ni(NO3)3·6H2O auxiliary metal salt is added to the main metal impregnation solution, and finally catalyst SS13 is obtained.
[0073] [Example 14]
[0074] The catalyst preparation method is the same as that in Example 1, except that 0.55 g of citric acid is added to 19.0 g of distilled water instead of 6.36 g of sodium carbonate being added to 200 g of distilled water, to finally obtain catalyst SS14.
[0075] [Example 15]
[0076] The catalyst preparation method is the same as that in Example 1, except that 0.55 g of citric acid is added to 19.0 g of distilled water instead of 1.70 g of sodium bicarbonate being added to 200 g of distilled water, to finally obtain catalyst SS15.
[0077] [Example 16]
[0078] The catalyst preparation method is the same as that in Example 5, except that the hydrothermal treatment temperature is adjusted to 150°C, and finally catalyst SS16 is obtained.
[0079] [Example 17]
[0080] The catalyst preparation method is the same as that in Example 5, except that the hydrothermal treatment time is adjusted to 24 h, and finally catalyst SS17 is obtained.
[0081] [Example 18]
[0082] The catalyst preparation method is the same as that in Example 5, except that the hydrothermal treatment temperature is adjusted to 220°C, and finally catalyst SS18 is obtained.
[0083] [Comparative Example 1]
[0084] At room temperature (25°C), 0.15 g of ammonium tungstate tetrahydrate ((NH4)6W7O 24·4H2O) was dissolved in 5mL H2O, stirred and dissolved, and then 5.0g of untreated Al2O3 carrier (the pseudo-boehmite in Example 1 was dried, cooled, ground to 200 mesh, and calcined at 550°C for 6h) was used for equal volume impregnation loading. After the subsequent aging, drying, calcination and post-sulfurization treatment steps similar to Example 1, the obtained catalyst was recorded as BJ1. It can be seen from the HRTEM image that the Al2O3 carrier is untreated and the loaded MoS2 nanosheets are in a multi-layer stacked state.
[0085] [Comparative Example 2]
[0086] At room temperature (25°C), 1.17 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) was dissolved in 5mL H2O, stirred and dissolved, and then 5.0g of untreated Al2O3 carrier (the pseudo-boehmite in Example 1 was dried, cooled, ground to 200 mesh, and calcined at 550°C for 6h) was used for equal volume impregnation loading, and the catalyst BJ2 was obtained after the same subsequent aging, drying, calcination and sulfurization treatment steps as in Example 1. It can be seen from the HRTEM image that the Al2O3 carrier is untreated and the loaded MoS2 nanosheets are in a multi-layer stacked state.
[0087]
Application examples
[0088] 1.0 g of the catalysts of Examples 1 to 18 and Comparative Examples 1 to 2 were weighed and loaded into a fixed bed reactor. The inlet temperature was 240°C, the pressure was 2.5 MPa, the hydrogen / oil volume ratio was 600:1, and the fresh oil volume space velocity was 2.0 h -1 Under the reaction conditions, HDN reaction was carried out on the simulated nitrogen- and sulfur-containing cracked gasoline component (a mixed solution of 30 ppmw pyridine and BTX, with benzene: toluene: xylene in BTX = 30:40:30 (molar ratio)). The denitrogenation and aromatic hydrogenation saturation rate in the reaction were analyzed. The results are shown in Table 2.
[0089] Table 1 Physicochemical properties of catalyst carrier (Al2O3) of examples and comparative examples
[0090] catalyst Carrier <![CDATA[Specific surface area / m 2 / g]]> B acid content / (μmol / g) SS1 <![CDATA[Al2O3-1.5]]> 252.6 5.7 SS2 <![CDATA[Al2O3-2.5]]> 285.6 7.4 SS3 <![CDATA[Al2O3-3.5]]> 305.8 8.6 SS4 <![CDATA[Al2O3-7.0]]> 322.6 10.7 SS5 <![CDATA[Al2O3-8.2]]> 350.0 15.1 SS6 <![CDATA[Al2O3-10.5]]> 330.7 22.6 SS14 <![CDATA[Al2O3-7.8]]> 331.3 12.8 SS15 <![CDATA[Al2O3-8.7]]> 342.2 13.8 SS16 <![CDATA[Al2O3-8.2]]> 297.4 18.2 SS17 <![CDATA[Al2O3-8.2]]> 362.5 9.9 SS18 <![CDATA[Al2O3-8.2]]> 367.7 8.6 BJ1 / BJ2 <![CDATA[Al2O3]]> 342.1 10.5
[0091] Table 2 Catalyst composition and catalytic performance evaluation results of each case
[0092]
[0093]
[0094] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A supported sulfide nanosheet catalyst, the chemical formula of the catalyst is M'-MS2 / Al2O3, wherein: M' is an auxiliary metal selected from at least one of the VIII group elements Fe, Co or Ni, M is a main metal selected from at least one of the VIB group elements Mo or W; more than 90% of the sulfide nanosheets are in a single-layer distribution state.
2. The catalyst according to claim 1, characterized in that: In the catalyst, based on the weight of the catalyst, the content of Al2O3 is 70% to 80%, the content of M in terms of oxide is 12% to 20%, and the content of M' in terms of oxide is 8% to 10%.
3. The catalyst according to claim 1, characterized in that: The sulfide nanosheet layer length is 2.0 to 20.0 nm, preferably 2.0 to 10.0 nm, and more preferably 2.0 to 5.0 nm.
4. The catalyst according to claim 1, characterized in that: The specific surface area of Al2O3 is 250~400m 2 / g, preferably 300 to 375 m 2 / g; the amount of B acid on the Al2O3 surface is 5 to 25 μmol / g, preferably 10 to 20 μmol / g, and more preferably 12.5 to 15.5 μmol / g.
5. A method for preparing the catalyst according to any one of claims 1 to 4, comprising: (1) Pseudo-boehmite is subjected to hydrothermal treatment, roasting and forming to obtain Al2O3; (2) loading metals M and M' on Al2O3, aging and calcining to obtain a catalyst precursor; (3) The catalyst precursor is subjected to sulfurization and reduction to obtain the catalyst.
6. The preparation method according to claim 5, characterized in that: In step (1), the average particle size of the pseudo-boehmite particles is 100 to 400 meshes, preferably 150 to 300 meshes.
7. The preparation method according to claim 5, characterized in that: In step (1), the hydrothermal treatment conditions are: temperature of 150-250°C, pH of 1.5-10.5, time of 4-24h, stirring speed of 200-800r / min, and heating rate to the hydrothermal treatment temperature of 0.5-2.0°C / min; preferably, the temperature is 150-200°C, the pH is 4.0-9.0, and the time is 4-12h; further preferably, the temperature is 180-200°C, the pH is 7.5-9.0, and the time is 6-12h.
8. The preparation method according to claim 5, characterized in that: In step (1), the calcination conditions are: temperature of 500-750°C, time of 3-8h, and heating rate of 0.5-4.0°C / min to the calcination temperature; And / or, in step (2), the aging temperature is 20 to 50° C., preferably 30 to 40° C., and the aging time is 4 to 48 hours, preferably 16 to 24 hours; And / or, in step (2), after aging, separation and drying are performed, wherein the drying conditions are: heating to 100-150° C. at 0.5-2° C. / min and drying for 8-24 h; And / or, in step (2), the calcination conditions are: the calcination temperature is 450-550°C, the calcination time is 3-8h, and the heating rate to the calcination temperature is 0.5-4°C / min.
9. The preparation method according to claim 5, characterized in that: In step (2), the main metal salt is ammonium molybdate tetrahydrate (NH4)6Mo7O 24 4H2O or ammonium tungstate hexahydrate (NH4) 6W7O 24 ·6H2O, and the auxiliary metal salt is selected from at least one of Fe(NO3)3·9H2O, Co(NO3)2·6H2O and Ni(NO3)2·6H2O.
10. The preparation method according to claim 5, characterized in that: The sulfurized oil used in sulfurization is prepared from dimethyl disulfide and cyclohexane, and the sulfur content is 400-5000ppm; And / or, the sulfurization / reduction pressure is 2.6-3.0 MPa, the volume ratio of hydrogen to catalyst precursor is (10-100):1; the volume space velocity of sulfurized oil is 3.0-5.0 h -1 The vulcanization temperature is 280-320°C and the vulcanization time is 20-40h.
11. Use of the catalyst according to any one of claims 1 to 4 in the hydrodenitrogenation reaction of pyrolysis gasoline.
12. The use according to claim 11, characterized in that: The reaction conditions of the hydrodenitrogenation reaction are: reaction temperature of 220-400°C, reaction pressure of 2.5-4.0 MPa, volume space velocity of 0.5-4.0 h -1 , the hydrogen / oil volume ratio is 500-700.
Citation Information
Patent Citations
Gasoline selective hydrogenation desulfurization catalyst, and preparation method and application of catalyst
CN107638882A
Catalytically cracked gasoline hydrodesulfurization catalyst and preparation method thereof
CN112371141A
Hydrodemetallization catalyst and preparation method thereof
CN116037137A
Supported hydrodesulfurization catalyst and preparation method thereof
CN116673044A
Hydrotreating catalyst and process for preparing the same
US20150209766A1